Slavomíra Ferenčuhová, Michaela Šuleřová, Barbora Vacková (eds.): Město [The City].: Sociální studia [Social Studies] 2/2006, Faculty of Social Studies, Masaryk University, Brno 2006, 227 pp., ISSN 1214-813X. - Novotná, Hedvika (Lidé města, 2007)
A review of the book by Slavomíra Ferenčuhová, Michaela Šuleřová and Barbora Vacková.